Critical care junior doctors' profile in a lower middle-income country: A national cross-sectional survey. - De Silva, A; Baranage, D; Padeniya, A; Sigera, P; De Alwis, S; Abayadeera, A; Mahipala, P; Jayasinghe, K; Dondorp, A; Haniffa, M (Medknow Publications, 2017)
Background and Aims Retention of junior doctors in specialties such as critical care is difficult, especially in resource‑limited settings. This study describes the profile of junior doctors in adult state intensive care units in Sri Lanka, a lower middle‑income country. Materials and Methods This was a national cross‑sectional survey using an anonymous self‑administered electronic questionnaire. Results Five hundred and thirty‑nine doctors in 93 Intensive Care Units (ICUs) were contacted, generating 207 responses. Just under half of the respondents (93, 47%) work exclusively in ICUs. Most junior doctors (150, 75.8%) had no previous exposure to anesthesia and 134 (67.7%) had no previous ICU experience while 116 (60.7%) ICU doctors wished to specialize in critical care. However, only a few (12, 6.3%) doctors had completed a critical care diploma course. There was a statistically significant difference (P < 0.05) between the self‑assessed confidence of anesthetic background junior doctors and non-anesthetists. The overall median competency for doctors improves with the length of ICU experience and is statistically significant (P < 0.05). ICU postings were less happy and more stressful compared to the last non‑ICU posting (P < 0.05 for both). The vast majority, i.e., 173 (88.2%) of doctors felt the care provided for patients in their ICUs was good, very good, or excellent while 71 doctors (36.2%) would be happy to recommend the ICU where they work to a relative with the highest possible score of 10. Conclusion Measures to improve training opportunities for these doctors and strategies to improve their retention in ICUs need to be addressed.